Child Physical Abuse from the Perspective of Pediatric Dentistry - Savin Carmen; Balan Adriana; Petcu Ana; Maxim A.; Earar K.; Balan Gh (Romanian Society of Oral Rehabilitation, 2010)
Child physical abuse is a complex problem, of great topical interest, a severe social problem, with direct implications on the dento-somato-facial harmony and on the psycho-mental and intellectual development of the child. Aim. To highlight the oro-maxillo-facial signs of physical abuse and the role of the pediatric dentists in identifying and evaluating this signs of physical abuse. Material and Method. The study was carried out on a sample of 299 abused subjects (218 boys and 81 girls) aged between 6-18 y.o. from Iasi rural and urban area. The data were analyzed and statistically processed and the results were synthesized with the help of a descriptive and correlative study. Results. The physical abuse has serious consequences in oro-dento-facial area, that consists especially in soft tissue lesions - 62.11%, dento-periodontal trauma (fractures, luxations, concussions, avulsions) - 19.47%, mandible fractures - 7.89% facial massif fractures - 7.89% and temporo-mandibular joint lesions - 2.63%. Conclusion. Pediatric dentist should to be legally qualified and morally entitled to report to report when s/he suspects any physical abuse against the child.